اللحن في الوقف وأثره في تغيير معاني القرآن - ستي, محمد الصالح (جامعة الوادي university of eloued, 2020)
ملخص البحث يُعرّف اللحن بأنه الإخلال والخطأ في تلاوة ألفاظ القرآن الكريم، وهو على قسمين: جلي وخفي، أما الوقف فهو قطع الصوت على الكلمة القرآنية زمنا يُتنفس فيه عادة، مع قصد الرجوع إلى القراءة. وقد عد علماء التجويد الخطأ في الوقف من قبيل اللحن الجلي، إذا ما أدى إلى إبهام معنى كلام الله تعـــــــــالى أو إفساده، وهذا ما يصطلح عليه بالوقف القبيح، وهو على قسمين: 1- ما لا يُفهم المراد منه لتعلقه اللفظي بما قبله: كالفصل بين الفعل وفاعله والمبتدأ وخبره. 2- ما يُفضي إلى معنى فاسدٍ أو مستقبحٍ لتعلقه المعنوي بما قبله: وأشنعه ما مس بقدسيّة الله عز وجل وصفاته، أو أخلّ بعقيدة المؤمن. Summary of the search: The solecism of Quran reciting is known as the breach and error in the recitation of the words of the Holy Quran. It is divided into two parts: clear and hidden, whereas the waqf is the cutting of the sound on the qur'aanic verse when it is usually breathed, with the intent to return reading. The scholars of Tajweed have considered the error in the waqf as a clear reciting solecism, if it leads to the ambiguity of the meaning of the words of Allah or its corruption, and this is what is termed as the ugly pause (stoppage at reciting), which is divided into two parts: 1 - What does not understand the meaning of the verbal attachment to what preceded: as the separation between the verb and its subject and the subject and its predicate. 2 - Which leads to the corrupt or repulsive meaning of moral attachment to what preceded it: and he did not touch the attributes and sanctity of Allah Almighty, or violated the faith of the believer
مقال
Keywords: اللحن ; قرآن ; جلي ; خفي